Partners in Public Health: Public Health Collaborations With Schools of Pharmacy, 2015. (May 2017) - DiPietro Mager, Natalie A.; Ochs, Leslie; Ranelli, Paul L.; Kahaleh, Abby A.; Lahoz, Monina R.; Patel, Radha V.; Garza, Oscar W.; Isaacs, Diana; Clark, Suzanne
To collect data on public health collaborations with schools of pharmacy, we sent a short electronic survey to accredited and preaccredited pharmacy programs in 2015. We categorized public health collaborations as working or partnering with local and/or state public health departments, local and/or state public health organizations, academic schools or programs of public health, and other public health collaborations. Of 134 schools, 65 responded (49% response rate). Forty-six (71%) responding institutions indicated collaborations with local and/or state public health departments, 34 (52%) with schools or programs of public health, and 24 (37%) with local and/or state public health organizations. Common themes of collaborations included educational programs, community outreach, research, and teaching in areas such as tobacco control, emergency preparedness, chronic disease, drug abuse, immunizations, and medication therapy management. Interdisciplinary public health collaborations with schools of pharmacy provide additional resources for ensuring the health of communities and expose student pharmacists to opportunities to use their training and abilities to affect public health. Examples of these partnerships may stimulate additional ideas for possible collaborations between public health organizations and schools of pharmacy.